Perspective: Milk and Dairy Provide Affordable High-Quality Protein and Merit Inclusion in the Protein Foods Group - Adam Drewnowski (Current Developments in Nutrition)
The United States Department of Agriculture (USDA) protein foods group includes meat, poultry, seafood, and several plant-based proteins—but not dairy. Yet milk, yogurt, and cheese provide affordable high-quality protein and multiple priority micronutrients. The present analyses compared dairy with Protein Group foods in terms of protein content and quality, nutrient density, and protein cost, using USDA nutrient composition databases and published national food prices. Protein quality was adjusted using Protein Digestibility Corrected Amino Acid Scores (PDCAAS). Nutrient density was assessed using the Nutrient Rich Food Index calculated per 100 kcal and per serving. Affordability was the cost of providing 1-oz equivalent of PDCAAS-corrected high-quality protein. Servings of milk, yogurt, and cheese provided 7 g of protein and were comparable with eggs and beans in terms of protein cost. The MyPlate 1-oz protein equivalency table ought to consider protein quality and ought to include dairy products as sources of dietary protein.